Influencia de los factores climaticos en la secrecion de nectar del naranjo valencia - Perez Piñeiro, A.=700 1 Garcia, O.; Abreu, A.C.
(Es, En)
Ilus., 6 ref.
Keywords: APICULTURA; FACTORES CLIMATICOS; TEMPERATURA; HUMEDAD RELATIVA; VELOCIDAD; NECTAR; SECRECION DE LAS PLANTAS; CITRUS SINENSIS; CUBA